Contribution of Media Based Learning on Traditional Culture Equipment for Student Motivation and Misconception - Z., Fakhruddin; Zulhelmi, Zulhelmi; Yennita, Yennita (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
The purpose of this study was to explore the contribution media based learning on traditional culture equipment on motivation and misconceptions of students. The method used is a quasi-experiment research was conducted in Kampar Junior High Schools of 121 students. Data Analysis that used is descriptive and inferential analysis. Based on the results of data analysis showed that the contribution of the media based learning on traditional culture equipment for increased motivation and to lower the misconception. This shows the media based learning on traditional culture-equipment can improve motivation and can reduce misconceptions of students.